Pseudomonas Cyclic Lipopeptides Suppress the Rice Blast Fungus Magnaporthe oryzae by Induced Resistance and Direct Antagonism - Omoboye, Olumide Owolabi; Oni, Feyisara Eyiwumi; Batool, Humaira; Yimer, Henok Zimene; De Mot, René; Höfte, Monica (Frontiers in Plant Science, 2019)
Beneficial Pseudomonas spp. produce an array of antimicrobial secondary metabolites such as cyclic lipopeptides (CLPs). We investigated the capacity of CLP-producing Pseudomonas strains and their crude CLP extracts to control rice blast caused by Magnaporthe oryzae, both in a direct manner and via induced systemic resistance (ISR). In planta biocontrol assays showed that lokisin-, white line inducing principle (WLIP)-, entolysin- and N3-producing strains successfully induced resistance to M. oryzae VT5M1. Furthermore, crude extracts of lokisin, WLIP and entolysin gave similar ISR results when tested in planta. In contrast, a xantholysin-producing strain and crude extracts of N3, xantholysin and orfamide did not induce resistance against the rice blast disease. The role of WLIP in triggering ISR was further confirmed by using WLIP-deficient mutants. The severity of rice blast disease was significantly reduced when M. oryzae spores were pre-treated with crude extracts of N3, lokisin, WLIP, entolysin or orfamide prior to inoculation. In vitro microscopic assays further revealed the capacity of crude N3, lokisin, WLIP, entolysin, xantholysin and orfamide to significantly inhibit appressoria formation by M. oryzae. In addition, the lokisin and WLIP biosynthetic gene clusters in the producing strains are described. In short, our study demonstrates the biological activity of structurally diverse CLPs in the control of the rice blast disease caused by M. oryzae. Furthermore, we provide insight into the non-ribosomal peptide synthetase genes encoding the WLIP and lokisin biosynthetic machineries..